Pengaruh Ekspor Migas, Ekspor Non Migas, PMA, Dan PMDN Terhadap Pertumbuhan Ekonomi Provinsi Jawa Timur - Ahmad Ali Ridwan; Syamsul Huda (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
Indonesia's economic development is never separated from economic growth, because economic development does not only cover economic growth, but also includes broader things such as changes in savings and investment as well as the structure of the economy. This study aims to analyze the effect of Oil and Gas Exports, Non Oil and Gas Exports, PMA, and PMDN on economic growth in East Java Province. The data used is secondary data taken from the Central Statistics Agency (BPS) in the period 2009-2020. Based on these objectives, the analytical method used is multiple regression analysis using the SPSS ver 26 program. The results obtained from this study are simultaneously the variables of Oil and Gas Exports, Non Oil and Gas Exports, PMA and PMDN have a significant influence on East Java's economic growth. However, partially Oil and Gas Exports, PMA and PMDN have a significant effect on East Java's economic growth and Oil and Gas Exports do not have a significant effect on East Java's economic growth.